From global trends to local realities: SOC accrual of improved management practices in northwestern Europe - Schepens, J.A.B.; Koopmans, C.J.; Heupink, D.T.; Timmermans, B.G.H.; Gentsch, N.; Martens, S.; de Haan, J.; Creamer, R.E.; Moinet, G.Y.K. (Geoderma Regional, 2025)
Numerous meta-analyses provide rates of carbon accrual for specific management practices at global scales. However, understanding how specific farming practices and soil properties influence SOC accrual within defined regions remains challenging. We examined whether three well-investigated improved management practices (organic fertilizer input, cover crops, and non-inversion tillage) increase SOC stocks within arable farming in Northwestern Europe. It was hypothesized that SOC accrual would be primarily driven by clay content. We sampled eleven experimental sites, where experimental durations, clay content, and SOC content ranged from 5 to 23 years, 1–20 %, and 0.9–2.3 %, respectively. The sites were sampled according to a uniform protocol for two depths (0–30 and 30–60 cm). Our cross-site analysis revealed substantial variation in SOC responses to the management practices, even within a single climatic region. There was a clear trend of increasing SOC accrual with increasing organic matter inputs from organic amendments, but effects were site dependent. Besides organic amendments, only frost-resistant cover crop species combined with non-inversion tillage accrued SOC at one site. Contrary to our hypothesis, clay content was not the primary driver of SOC accrual. Instead, SOC accrual was most strongly driven by the interplay between experimental duration and the initial SOC stock. Our study underscores the need for context-specific SOC management strategies that account for the initial SOC levels.